Home » Logarithm Quotient Rule

Logarithm Quotient Rule

The logarithm quotient rule is:

logb(x/y) = logb(x) – logb(y)

b, x, y ∈ R+, b ≠ 1

R+ denotes the set of positive real numbers.

Logarithm Quotient Rule Proof

logb(x/y) = logb(xy-1)

We apply the logarithm product rule:

logb(xy-1) = logb(x) + logby-1)

We apply the logarithm power rule:

logb(xy-1) = -1 · logby = – logby

⇒ logb(x/y) = logbx – logby

Logarithm Quotient Rule Examples

log10(1/100) = log10(1) – log10(100) = 0 – 2 = -2

log(1000) = log(10000/10) = log(10000) – log(10) = 4 – 1 = 3

Binary Log Quotient Rule Examples

log2(x/y) = log2(x) – log2(y)

log2(1/8) = log2(1) – log2(8) = 0 – 3 = -3 log2(0.0625) = log2(1/16) = log2(1) – log2(16) = 0 – 4 = -4

Natural Log Quotient Rule Examples

ln(x/y) = ln(x) – ln(y)

ln(e/π) = ln(e) – ln(π) = 1 – 1.1447298858 = -0.14472988584 ln(2/3) = ln(2) – ln(3) = 0.6931471805 – 1.0986122886 = -0.4054651081

Frequently Asked Questions

Click on the question which is of interest to you to see the collapsible content answer.

What is the quotient property of logarithms formula?

log(x/y) = log(x) – log(y)

How to prove the quotient rule of logarithms?

First apply the logarithm product rule, then make use of the logarithm power rule.

What is the quotient rule for logarithms?

The quotient rule for logarithms states that the log of a quotient equals the difference of the log of the dividend and the log of the divisor.

Summary


If you have not already done so, please hit the share buttons, and install our PWA app (see sidebar or menu).

If you still do things the traditional way: bookmark us now!

BTW: Here’s the Change of Base Law.

Thanks for your visit!